2017
DOI: 10.1007/s13105-017-0575-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 2000-m running test on antioxidant and cytokine response in plasma and circulating cells

Abstract: Exercise intensity usually correlates with increased oxidative stress and enhanced cytokine production. However, it is unknown if all types of exercise that induce muscle damage can cause a parallel response in the oxidation balance and cytokine production. To this end, the effect of a 2000-m running test in a group of volunteers that regularly train in aerobic routines was studied. Different circulating parameters were measured, oxidative stress markers (protein carbonyls and malondialdehyde), antioxidant enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…However, in the present study, no significant differences in the expression of the studied cytokines were detected related to exercise performance after the 2000-m test. A similar result was observed in a previous study [20]. This could be due to the extremely short half-life of the messengers in plasma, or that their release did not coincide with the moment that the blood sample was extracted.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…However, in the present study, no significant differences in the expression of the studied cytokines were detected related to exercise performance after the 2000-m test. A similar result was observed in a previous study [20]. This could be due to the extremely short half-life of the messengers in plasma, or that their release did not coincide with the moment that the blood sample was extracted.…”
Section: Discussionsupporting
confidence: 88%
“…Certain stress situations that appear during intense sport performance are accompanied by increases in oxidative stress and inflammatory responses [1]. In a previous report [20], it was revealed that a 2000-m running test could be considered as a valid method to assess oxidative stress in individuals that are accustomed to train in aerobic routines. At the end of the test, the participants presented increased oxidative stress and muscle damage [20], confirming the results observed in other studies [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations